Development of Sour Cherry Nectar Enriched With Basil Leaf Extract - Otmankhil , Noorzai; Salari, Hamid; Amin, Mohammadullah; Habibi, Mahboobullah; Qurishi, Hikmatullah; Sediqi, Mohamad Waris; Stanikzai, Ramin; Ahadi, Mohammad Sabor (Journal of Natural Sciences – Kabul University, 2025)
This study was conducted in 2025 at the Horticulture Department Laboratory, Faculty of Agriculture, Kabul University, with the objective of formulating sour cherry Local (AFG 0351) nectar enriched with basil leaf extract. The experiment was arranged in a split-plot CRD design with eight treatments and three replications during a 60-day storage period. Chemical parameters (TSS, titratable acidity, pH, reducing sugars, non-reducing sugars, and total sugars), biological attribute (spoiled nectars), sensory properties (appearance, aroma, flavor, color, and overall acceptability), and economic assessment. Results indicated that increasing the proportion of basil leaf extract reduced TSS, acidity, and sugars content, while pH increased. Sensory scores were also improved. Furthermore, prolonged storage led to an increase in TSS, pH, sugar, and sensory attributes, whereas non-reducing sugars decreased. The best treatment was 6% basil leaf extract + 94% sour cherry juice, with a benefit-cost ratio of 1.45:1 AFN, and is therefore recommended as the optimal formulation.